1998
DOI: 10.1093/jjco/28.6.364
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in the Management of Graves' Ophthalmopathy

Abstract: Background:To report the results of radiotherapy for patients with failure, adverse reactions or relative contraindications to the use of steroids or immunosuppressants, by using newly developed quantitative indexes. Methods: Fourteen female and six malepatients withGraves' ophthalmopathy weretreated with radiotherapy between 1989 and 1996. Priorto radiotherapy, eightpatients received treatment with prednisone, four received immunosuppressants and four received a combination of both. Four patients with contrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Late complications following radiotherapy of retrobulbar area include: retinopathy, cataract and radiation-induced tumours [9, 1315, 17, 23, 24, 26, 29, 42, 43, 45, 46, 51, 59, 61, 65, 66, 68, 73]. In the presented material, three cases of cataract (three out of 106 = 2.8%) were reported that however might have been related to the physiological ageing process and not to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late complications following radiotherapy of retrobulbar area include: retinopathy, cataract and radiation-induced tumours [9, 1315, 17, 23, 24, 26, 29, 42, 43, 45, 46, 51, 59, 61, 65, 66, 68, 73]. In the presented material, three cases of cataract (three out of 106 = 2.8%) were reported that however might have been related to the physiological ageing process and not to radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The following factors are considered to worsen the prognosis of ophthalmopathy: patient age above 50–60 years, male sex, smoking, symptom duration, concomitant diabetes, hyperthyreosis [2, 5, 8, 9, 13, 14, 25, 26, 30, 32, 45, 49, 51, 52, 58, 59, 70]. The effect of these factors was analysed in the group of patients treated with the most effective method, i.e.…”
Section: Discussionmentioning
confidence: 99%